Training for Preparing, Filling and Reporting of Tax Return at WITA Jakarta - Waluyo Waluyo; Deden Tarmidi; Noor Hazlina Ahmad (MOVE: Journal of Community Service and Engagement, 2023)
MSMEs (Micro, Small and Medium Enterprises) in Indonesia are growing rapidly from year to year and are a group that strongly supports the development of the Indonesian economy as a whole. Even so, the compliance of MSMEs as Non-Employee Individual Taxpayers is quite low, this is due to the limited human resources owned by MSME actors in understanding tax regulations and carrying out tax obligations including in the preparation of Annual Tax Return reporting and reporting. Due to these limitations, this Community Service project is carried out to raise WITA Jakarta MSMEs' tax literacy, especially in the preparation of the Annual Tax Return and its reporting so that it can help MSMEs as compliant taxpayers and assist the state in disseminating information on tax regulations to increase tax revenue